How toTeach a Second Language in the Classroom? Benefits Associated with the CLIL Approach - Bolarín-Martínez, María José; Porto-Currás, Mónica; Lova-Mellado, María (Revista Electrónica Educare, 2021)
Introduction. This article discusses how the Content and Languages Integrated Learning (CLIL) favors the construction of bilingual learning that brings different benefits to students. Aims. This research aims to assess whether the conceptual, methodological, and cultural changes, brought by the teaching of a second language through the CLIL approach, involve not only an improvement in the learning done by students but also a review and renewal of the teaching practice of the teachers involved. Analysis. To accomplish this aim, the article considers the CLIL approach’s conceptualization and a detailed analysis of the methodological strategies that teachers should employ to facilitate the implementation of this approach in the classroom. Conclusions. The review of these methodological strategies leads to results and conclusions that, in order to develop them in practice, teachers have to reflect deeply on the teaching they are doing and the objectives they intend to achieve. If this reflection is generated and generalized among all the teachers participating in Bilingual Teaching Programs, many of the pedagogical challenges claimed for compulsory education for decades will be being achieved, allowing both the renewal of language teaching and the system educational in general.